A COMPARATIVE STUDY OF CAUDAL BLOCK AND ULTRASOUND-GUIDED TRANSVERSUS ABDOMINIS PLANE BLOCK WITH LEVOBUPIVACAINE AND DEXAMETHASONE AS ADDITIVE IN EXTRAPERITONEAL LOWER ABDOMINAL SURGERIES IN PEDIATRICS - GHODKE, SANDHYA; RAVINDRA, MADHAVI; RN, HIREMATH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to evaluate the efficacy of ultrasound-guided transversus abdominis plane (TAP) block versus caudal block for post-operative analgesia with levobupivacaine and dexamethasone as additive in extraperitoneal lower abdominal surgeries in pediatrics as there is no available literature showing the same. Methods: This is a randomized control study carried out between two groups among 50 children (1–8 years of age), both sexes, posted for elective extraperitoneal lower abdominal surgeries after taking informed consent from parents. Fifty children were randomly allocated into two groups, 25 in each group. Caudal epidural (CE) group received general anesthesia and caudal block with 1 ml/kg of 0.2% levobupivacaine and 0.1 mg/kg dexamethasone. TAP group received general anesthesia and ultrasound-guided TAP block with 0.5 ml/kg of 0.2% levobupivacaine and 0.1 mg/kg dexamethasone. Data were collected by means of pre-designed format with pre-/post-operative assessment with standardized scores. Results: The mean age of the patients was 4.84 (SD=2.29). Mean face, legs, activity, cry, and consolability score was low and non-significant before shifting the patient (<2 h post-operative [post-op]) in both the groups. Thereafter from 2 to 12 h, the mean score increased to 4.92 (SD=2.72) in the CE group and 2.92 (SD=2.17) in the TAP group and the difference was statistically significant at 2 h, 4 h, 6 h, and 12 h postoperatively. Mean time to rescue analgesia in the CE group was 4.96 h (SD=4.32) and 5.52 h (SD=7.53) in the TAP group and difference was statistically significant (p=0.000). Mean total rescue analgesic requirement for the CE and TAP groups was 298.40 mg (SD=170.70) and 111.40 mg (SD=138.81) and the difference was also significant. Post-operative complications such as urinary retention and motor blockade were seen in 28% of CE patients, while none of the patients experienced post-operative nausea/vomiting. Conclusions: Our study showed significant increase in duration of post-operative analgesia among TAP patients with reduced requirement of rescue analgesics and lesser post-operative complications as compared to CE patients